PENGARUH MODAL ASING, KURS, INFLASI, SUKU BUNGA DAN INDEKS SAHAM TERHADAP KAPITALISASI PASAR MODAL INDONESIA - Pudji Astuty; Almira Rizqia (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2021)
The goal of this research is to examine the impact of Foreign Investment, Exchange Rate, Inflation, Interest Rates, Stock Index on Indonesian Capital Market Capitalization. The research was processed using the SPSS 22 program with multiple linear regression. The data used uses two types of periods, namely the period 1990-2019 and the period 1990-2020 to see the differences due to the Covid-19 Pandemic in 2020. From the results of the research, it is known that Foreign Investment, Exchange Rate and Stock Index have a significant positive effect on Indonesia's Capital Market Capitalization. for both periods. Meanwhile, Interest Rates only had a negative effect in the period 1990-2020 and Inflation had no effect on both periods.